Biodegradable flexible proton conducting solid biopolymer membranes based on pectin and ammonium salt for electrochemical applications. (15th February 2023) - Muthukrishnan, M.; Shanthi, C.; Selvasekarapandian, S.; Premkumar, R.
Abstract: One of the most significant difficulties confronting civilization today is the availability of renewable power generation for a growing and highly productive society. Solid-state batteries are expected to be advantageous in a wide variety of energy storage systems. The present work examines the synthesis and characterization of solid biopolymer membranes as electrolytes for solid-state primary proton battery applications from the viewpoint of renewable energy development. Solid biopolymer membranes (SBPMs) based on anionic polysaccharide host polymer pectin and proton donor ammonium iodide (AI) salt are synthesized via a facile solution cast technique. The impact of dopant salt concentration (30 M.wt % to 80 M.wt %) on the membranes' electrical, dielectric, transport, thermal, structural, and electrochemical properties was investigated. At ambient temperature, a maximum ionic conductivity of 4.5 × 10 −3  S cm −1  has been achieved. The dielectric and transport properties of the prepared SBPMs are studied and correlated with the trend of ionic conductivity. With the highest conductive SBPM, the primary proton battery has been assembled. The discharge performance and open circuit voltage (OCV) were examined and recommended as a potential candidate for alternate research for low power density applications. Highlights: Flexible, eco-friendly proton-conducting biopolymer membranes are prepared. The highest conducting membrane exhibit ionic conductivity of 4.5 × 10 −3  S cm −1 . Ionic conductivity of the samples is correlated with the dielectric and transport properties. A primary proton battery was built using the membrane as an electrolyte. The fabricated proton battery assembly has an OCV of 1.48 V.